2004
DOI: 10.1021/ac035030+
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Poly(methyl methacrylate) Microfluidic Chips by Atmospheric Molding

Abstract: While the new approach is demonstrated in connection with PMMA microchips, it could be applied to other materials that undergo light-initiated polymerization. The new approach brings significant simplification of the process of fabricating PMMA devices and should lead to a widespread low-cost production of high-quality separation microchips.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(87 citation statements)
references
References 25 publications
1
84
0
2
Order By: Relevance
“…do Lago and co-workers [87] demonstrated that a low cost electrophoretic microchip for CCD can be fabricated by depositing a thin layer of laser printer toner on a polyester film, which is then laminated with another polyester film of the same dimensions. Muck et al [91] demonstrated a new approach to the fabrication of PMMA-chips to be used with CCD which consists of UV-polymerization of a monomer in contact with a negative master of the desired structures. A range of applications of microchip electrophoresis with CCD has been reported.…”
Section: Contactless Conductivity Detection In Microchip Electrophoresismentioning
confidence: 99%
“…do Lago and co-workers [87] demonstrated that a low cost electrophoretic microchip for CCD can be fabricated by depositing a thin layer of laser printer toner on a polyester film, which is then laminated with another polyester film of the same dimensions. Muck et al [91] demonstrated a new approach to the fabrication of PMMA-chips to be used with CCD which consists of UV-polymerization of a monomer in contact with a negative master of the desired structures. A range of applications of microchip electrophoresis with CCD has been reported.…”
Section: Contactless Conductivity Detection In Microchip Electrophoresismentioning
confidence: 99%
“…The channel had trapezoidal shape with 40 mm (bottom) and 100 mm (top) widths and a 50 mm depth. The PMMA microchips were prepared in our laboratory according to a recently reported procedure [21]. Briefly, a silicon master was prepared by pattern transfer techniques including soft lithography and wet chemical etching and used as a negative template to create the desired channel structure.…”
Section: Microchip Fabricationmentioning
confidence: 99%
“…Essa classe de compostos desempenha um papel fundamental no sistema nervoso central atuando como neurotransmissores. Trabalhos que têm como objetivo apresentar novas técnicas de microfabricação ou sistemas de detecção geralmente apresentam separações de catecolaminas como compostos modelos [131][132][133] . A determinação simultânea de dopamina, norepinefrina, L-DOPA, DOPAC e ácido ascórbico em amostras de plasma, foi realizada por Johirul e colaboradores 134 usando eletroforese de zona em microdispositivos construídos em vidro.…”
Section: Análise De Pequenas Moléculasunclassified